2013
DOI: 10.1289/ehp.1205588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Doses of Bisphenol A on the Metabolome of Perinatally Exposed CD-1 Mice

Abstract: Background: Bisphenol A (BPA) is a well-known endocrine disruptor used to manufacture polycarbonate plastics and epoxy resins. Exposure of pregnant rodents to low doses of BPA results in pleiotropic effects in their offspring.Objective: We used metabolomics—a method for determining metabolic changes in response to nutritional, pharmacological, or toxic stimuli—to examine metabolic shifts induced in vivo by perinatal exposure to low doses of BPA in CD-1 mice.Methods: Male offspring born to pregnant CD-1 mice th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 51 publications
(59 reference statements)
7
78
1
2
Order By: Relevance
“…These alterations provide the presynaptic mechanism of impaired LTP by BPA exposure. The above findings corroborate previous researches showing that perinatal BPA exposure results in less glutamate release from presynaptic neurons 32. Therefore, the presynaptic site in the hippocampus is susceptible to both perinatal and juvenile BPA exposure.…”
Section: Discussionsupporting
confidence: 92%
“…These alterations provide the presynaptic mechanism of impaired LTP by BPA exposure. The above findings corroborate previous researches showing that perinatal BPA exposure results in less glutamate release from presynaptic neurons 32. Therefore, the presynaptic site in the hippocampus is susceptible to both perinatal and juvenile BPA exposure.…”
Section: Discussionsupporting
confidence: 92%
“…GABAergic tone appeared to be increased after BPA exposure in some studies (34,37) or reduced in others (36,38,39). In a recent study close to our conditions using whole brain extracts from animals exposed to different doses of BPA from gestational day 8 to PND16, Cabaton et al (36), investigated brain composition by nuclear magnetic resonance spectroscopy on PND21. In this non targeted metabolomics study, these authors reported that 25 g/kg⅐d of BPA could reduce GABA concentrations in the brain.…”
Section: Discussionsupporting
confidence: 52%
“…Developmental exposure to these endocrine disrupting chemicals (EDCs) can result in a permanent change in the regulation of insulin and glucose levels [2]. EDCs may also impact metabolism through effects on the neuroendocrine systems that control feeding as well as other behaviors [79]. Importantly, some neural and metabolic effects due to fetal exposure to EDCs are observed during specific periods during postnatal life, such as during early adolescence [10], adulthood [11] or middle age [12].…”
Section: Introductionmentioning
confidence: 99%